Rapid qualitative and quantitative HPLC/MS analysis of an antioxidant couple consisted of glutathione and ascorbic acid in a pharmaceutical product - Stanislav V. Yefimov (GarVal Editorial Ltda., 2021)
Context: In pharmacy products, glutathione and vitamin C are often present together. Both components not only enhance each other's action but also protect each other from oxidation, forming an antioxidant couple. The work is devoted to the development of an HPLC method for determining the activity of pharmaceutical preparations containing the antioxidant couple as an active substance. Aims: Develop and validate an HPLC/MS method for the determination of an antioxidant couple of glutathione and ascorbic acid in pharmaceutical products. The method should be fast and simple, that is, analyze both components in one run without derivatization and any preliminary sample preparation. Methods: The Agilent 6125 C SQ LS/DAD/MS instrument was used to detect the two active components simultaneously. MSD was used to detect glutathione; DAD was used to detect ascorbic acid. Results: The run time was 2.0 min. Glutathione was eluted with a retention time of 1.48 min. Its limit of detection was 0.03 μg. Ascorbic acid was eluted with a retention time of 1.02 min. Its limit of detection was 0.01 μg. Recovery of glutathione varied from 92 to 105%, and the recovery of ascorbic acid varied from 99 to 100%. In positive electrospray ionization mode, the spectra of glutathione (Glut.) showed the predominant signals at m/z+ of 308.2, which corresponds to cation (Glut.-H+). Ascorbic acid(AA) is converted into several cations, including AA-H+ and 2AA-Na+, m/z+= 177 and 375. Conclusions: The developed HPLC/MS method for the determination of antioxidant couple consisted of glutathione and ascorbic acid in nasal spray and injection solution was validated for accuracy/recovery, precision, and selectivity. The use of a tandem of a mass spectrometric detector and a diode-array detector is substantiated. The method is fast, simple, sensitive and reproducible, and is suitable for the determination of the antioxidant couple in pharmaceutical products without derivatization or any preliminary sample preparation.